Characteristics of the Spatial Structure of Traditional Villages in the Xinjiang Uygur Autonomous Region in China and Their Influence Mechanisms - Yanlong Guo; Siqi Zhai; Jie Huang; Haoyuan Guo (Buildings)
Traditional villages are one of the basic types of rural revitalisation and one of the important carriers of cultural inheritance. This research is based on the data of 53 traditional villages in the Xinjiang Uyghur Autonomous Region with the aid of the ArcGIS10.8.1 spatial analysis platform. The study identifies the spatial evolution characteristics from the spatial distribution type, distribution direction, distribution density, distribution balance, etc., and explores their influence mechanisms. The study shows that 1. the spatial structure of traditional villages in Xinjiang was analysed as a cohesive structure type by using the nearest neighbour index method, which shows the evolutionary characteristics of the agglomerative tendency to increase gradually. Among them, Changji Hui Autonomous Prefecture and Turpan City have the highest degree of concentration. 2. The establishment and development of traditional villages in Xinjiang is mainly influenced by natural factors such as geographical features and hydrography. Social factors such as population distribution, transport conditions and economic progression have very important implications for the preservation and continuation of traditional villages.